2019
DOI: 10.1002/j.2334-5837.2019.00622.x
|View full text |Cite
|
Sign up to set email alerts
|

12 principles for SE leaders

Abstract: This paper describes 12 leadership principles to follow when building an Systems Engineering (SE) Capability. Successful Systems Engineering leadership requires the fusion of systems engineering and leadership. Based upon the authors' experience in Defence, Rail, Information Services, Healthcare, Medical Devices, Power and Manufacturing, this paper describes practical approaches to: Make and sustain the case for SE. Ensure that SE contributes to the business and that it is supported by key stakeholders. Estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…Specifically, there were nine papers that highlighted the necessary teamwork attributes required in industry and three papers in Academia. From the industry perspective, different systems engineering competency models presented the important teamwork characteristics a systems engineer should possess in the engineering discipline [31], [32], [34], [36], [40]. For example, the US Department of Defense has created a comprehensive systems engineering competency model that mentions teamwork attributes including commitment to goals and mission, managing the group process by leading and building teams and providing technical direction for use in defense acquisition [32].…”
Section: Teamwork Attributesmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, there were nine papers that highlighted the necessary teamwork attributes required in industry and three papers in Academia. From the industry perspective, different systems engineering competency models presented the important teamwork characteristics a systems engineer should possess in the engineering discipline [31], [32], [34], [36], [40]. For example, the US Department of Defense has created a comprehensive systems engineering competency model that mentions teamwork attributes including commitment to goals and mission, managing the group process by leading and building teams and providing technical direction for use in defense acquisition [32].…”
Section: Teamwork Attributesmentioning
confidence: 99%
“…Leslie [31] presented an engineering competency model that promotes an understanding of the global systems engineering skill sets where teamwork attributes including open and effective communication, commitment to team objectives and goals, psychological safety and building interpersonal relationships were emphasized. For a successful systems engineering leadership, Kemp et al [34] suggested useful principles that would help guide practitioners developing effective systems engineering teams. Team composition was one of the most important teamwork attributes highlighted where selecting team members with the right attitudes, beliefs and culture is important for the success and sustainability of a systems engineering team.…”
Section: Teamwork Attributesmentioning
confidence: 99%